FixThePig: a custom 3D-printed femoral intramedullary nailing for preclinical research applications - Manon, Julie; Englebert, Alexandre; Evrard, Robin; Schubert, Thomas; Cornu, Olivier (Frontiers in Bioengineering and Biotechnology, 2024)
Background Critical-size bone defects (CSBDs) pose significant challenges in clinical orthopaedics and traumatology. Developing reliable preclinical models that accurately simulate human conditions is crucial for translational research. This study addresses the need for a reliable preclinical model by evaluating the design and efficacy of a custom-made 3D-printed intramedullary nail (IMN) specifically for CSBDs in minipigs. The study aims to answer the following questions: Can a custom-made 3D-printed IMN be designed for femoral osteosynthesis in minipigs? Does the use of the custom-made IMN result in consistent and reproducible surgical procedure, particularly in the creation and fixation of CSBDs? Can the custom-made IMN effectively treat and promote bone consolidation of CSBDs? Hypothesis The custom-made 3D-printed IMN can be designed to effectively create, fix and treat CSBDs in minipigs, resulting in consistent surgical outcomes. Materials and Methods The IMN was designed based on CT scans of minipig femurs, considering factors such as femoral curvature, length, and medullary canal diameters. It was 3D-printed in titanium and evaluated through both in vitro and in vivo testing. Female Aachen minipigs underwent bilateral femoral surgeries to create and fix CSBDs using the custom-made IMN. Post-operative follow-up included X-rays and CT scans every 2 weeks, with manual examination of explanted femurs to assess consolidation and mechanical stability after 3 months. Results The custom-made IMN effectively fitted the minipig femoral anatomy and facilitated reproducible surgical outcomes. Symmetric double osteotomies were successfully performed, and allografts showed minimal morphological discrepancies. However, proximal fixation faced challenges, leading to non-union in several cases, while most distal osteotomy sites achieved stable consolidation. Discussion The custom-made 3D-printed IMN demonstrated potential in modelling and treating CSBDs in minipigs. While the design effectively supported distal bone healing, issues with proximal fixation highlight the need for further refinements. Potential improvements include better screw placement, additional mechanical support, and adaptations such as a reduction clamp or a cephalic screw to enhance stability and distribute forces more effectively.